Lithium-sulfur battery diaphragm with spherical-chain-shaped metal oxide structure and preparation method of lithium-sulfur battery diaphragm

By using ternary composite materials and metal oxide nanoparticles with spherical chain metal oxide structure in lithium sulfur battery separators, the capacity reduction and safety risks caused by lithium polysulfide are solved, and the cycle stability of the battery is significantly improved and rate performance.

CN119401056AActive Publication Date: 2025-02-07NANTONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411552281.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-07
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The dissolution of lithium polysulfide in lithium sulfur batteries leads to a decrease in capacity, low Coulomb efficiency and poor rate performance. The shuttle effect increases the internal resistance of the battery, and lithium dendrites cause problems such as overheating, fire or explosion.

Method used

The lithium sulfur battery separator with a spherical chain metal oxide structure is adopted. The chain conductive material and spherical metal oxide ternary composite material on the sulfur cathode side suppress the shuttle effect, and the metal oxide nanoparticles on the anode side uniformly distribute the lithium branches. Crystal growth.

Benefits of technology

Significantly inhibit the polysulfide shuttle effect, improve the diffusion efficiency of lithium ions, improve the cycle stability and rate performance of the battery, enhance the electrochemical performance, and reduce overheating and safety risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119401056A_ABST
    Figure CN119401056A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium-sulfur battery diaphragm with a spherical-chain-shaped metal oxide structure and a preparation method of the lithium-sulfur battery diaphragm, and belongs to the technical field of membrane preparation. Wrapping the hammer-shaped metal oxide with a conductive polymer to obtain a metal oxide hammer-shaped ternary composite material; mixing the metal oxide hammer-shaped ternary composite material with a PVDF (Polyvinylidene Fluoride) adhesive according to a certain mass ratio, coating a polypropylene film with the mixture, and drying; and dispersing the metal oxide nanoparticles in an ethanol solution, and carrying out suction filtration to the back surface of the diaphragm, so as to prepare the lithium-sulfur battery diaphragm with a spherical-chain-shaped metal oxide structure. The diaphragm can slow down the shuttle effect of polysulfide and inhibit the growth of lithium dendrites, and can be used for improving the stability and capacity of the lithium-sulfur battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium-sulfur battery separator preparation, and in particular relates to a lithium-sulfur battery separator with a ball-chain metal oxide structure and a preparation method thereof. Background Art

[0002] Lithium-sulfur batteries are a potential choice for next-generation energy storage because of their high theoretical specific capacity (1675 mAh g -1 ), high energy density (2600Wh kg -1 ) and lower cost. However, the widespread application of lithium-sulfur batteries faces various challenges. The dissolution of lithium polysulfides (LiPSs) in organic electrolytes is a key issue, which can lead to severe capacity degradation, low Coulombic efficiency and poor rate performance. During the battery charge and discharge process, LiPSs will shuttle back and forth between the positive and negative electrodes, forming the so-called "shuttle effect", which will not only cause the loss of active materials but also increase the internal resistance of the battery, thereby affecting the performance and life of the battery. The formation of lithium dendrites is another major challenge. During the battery charge and discharge process, lithium ions are unevenly deposited on the negative electrode, which easily forms lithium dendrites. These lithium dendrites will continue to grow and pierce the battery separator, resulting in direct contact between the positive and negative electrodes, causing a short circuit, and may even cause the battery to overheat, catch fire or explode. These problems have seriously hindered the commercial development of lithium-sulfur batteries. Summary of the invention

[0003] Technical issues solved:

[0004] The present application aims at the deficiencies in the prior art and solves the technical problems that lithium polysulfides can cause serious capacity decline, low Coulomb efficiency and poor rate performance, the shuttle effect causes an increase in battery internal resistance, thereby affecting the performance and life of the battery, and lithium dendrites can cause battery overheating, fire or explosion. The application provides a lithium-sulfur battery separator with a spherical chain metal oxide structure and a preparation method thereof. The separator can inhibit the shuttle effect and lithium dendrite growth, and improve the ionic conductivity, enhance the diffusion efficiency of lithium ions, improve the cycle stability and rate performance of the lithium-sulfur battery, and improve the electrochemical performance of the lithium-sulfur battery.

[0005] Technical solution:

[0006] To achieve the above objectives, this application is implemented through the following technical solutions:

[0007] The preparation method of a lithium-sulfur battery separator having a ball-chain metal oxide structure comprises the following steps:

[0008] The first step: dissolving 2-4 g of metal salt in 80-100 mL of deionized water according to the mass-to-volume ratio, adding acid to adjust the pH value to 0.68 to obtain a metal salt solution, and then immersing 40-60 mg of chain-shaped conductive material in the metal salt solution, stirring for 1 hour, centrifuging, washing and dispersing in 50 mL of deionized water to obtain a dispersion, and transferring the dispersion to a RC-HP-CV high-pressure variable volume reactor for hydrothermal treatment. When the reactor temperature drops to room temperature, the black product after the hydrothermal treatment is collected, washed three times with deionized water and anhydrous ethanol, and transferred to a vacuum drying oven for drying to obtain a precursor of a chain-shaped metal oxide;

[0009] Step 2: Grind the precursor of the chain ball-shaped metal oxide and place it on a quartz boat, and then place the quartz boat in a tube furnace, and then calcine it in an air environment for 2 hours, and after cooling, obtain the chain ball-shaped metal oxide powder;

[0010] Step 3: prepare a mixed solution of concentrated hydrochloric acid and deionized water at a volume ratio of 1:38-40, take 39-41 mL of the mixed solution and divide it into two equal parts and place them in two beakers, respectively denoted as A and B, drip 200-300 μL of conductive polymer monomer into beaker A drop by drop and ultrasonically treat it, and disperse the chain ball-shaped metal oxide powder into the ultrasonically treated solution; add 0.5-0.7 g of ammonium persulfate into beaker B and stir to dissolve, then drip the solution into beaker A drop by drop, finally stir for 4 hours, and then obtain the metal oxide chain ball-shaped ternary composite material after centrifugation, washing and drying;

[0011] Step 4: Dissolve 2-4 g of metal salt in 80-100 mL of deionized water according to the mass-to-volume ratio, add acid to adjust the pH value to 0.68 to obtain a metal salt solution, stir for 1 hour, centrifuge, wash and disperse in 50 mL of deionized water to obtain a dispersion, transfer the dispersion to a RC-HP-CV high-pressure variable volume reactor, perform hydrothermal treatment, collect the product after hydrothermal treatment after the reactor temperature drops to room temperature, wash three times with deionized water and anhydrous ethanol, transfer to a vacuum drying oven, and dry to obtain a precursor of metal oxide nanoparticles;

[0012] Step 5: Grind the precursor of the metal oxide nanoparticles and place it on a quartz boat, place the quartz boat in a tube furnace, and then calcine it in an air environment for 2 hours, and then cool it to obtain the metal oxide nanoparticles;

[0013] Step 6, preparation of slurry: magnetically stirring the metal oxide chain ball-shaped ternary composite material and the polyvinylidene fluoride PVDF binder to prepare a slurry after mixing evenly;

[0014] Step 7: Use a mold to evenly coat the slurry on the commercial PP diaphragm Celgard 2500, and then transfer the Celgard 2500 diaphragm to a drying oven to obtain a metal oxide chain ball-shaped ternary composite diaphragm;

[0015] Step 8: Disperse 0.5 g of metal oxide nanoparticles in 50 mL of anhydrous ethanol solution according to the mass volume ratio to form a uniform suspension, and then filter the suspension to the back of the metal oxide chain ball-shaped ternary composite membrane with a suction filtration bottle, and then transfer the membrane to a vacuum drying oven and dry it at 40 ° C for 4 hours;

[0016] Step 9, preparation of the diaphragm: Cut the diaphragm dried in step 8 into small discs with a diameter of 19 mm to obtain a lithium-sulfur battery diaphragm with a ball-chain metal oxide structure.

[0017] Furthermore, the metal oxide is one or more of tin oxide, iron oxide, aluminum oxide, vanadium pentoxide, niobium pentoxide, and titanium dioxide; the chain-like conductive material is one or more of carbon nanotubes, carbon fibers, silver nanowires, silicon carbide nanowires, and titanium nanowires; the conductive polymer is one or more of polyaniline, polypyrrole, and polyacetylene; the metal salt is one or more of stannous chloride dihydrate, ferric chloride, aluminum chloride hexahydrate, and niobium pentachloride; the acid is concentrated hydrochloric acid, and the concentrated hydrochloric acid is 37% concentrated hydrochloric acid.

[0018] Furthermore, the hydrothermal process is specifically as follows:

[0019] Stage 1: The temperature was raised from room temperature to 120°C at a rate of 5°C / min, the reactor volume was maintained at 65mL, and the time was 20 minutes;

[0020] The second stage: the temperature was increased from 120°C to 190°C at a heating rate of 2°C / min, the reactor volume was increased from 65mL to 85mL, and the time was 70 minutes;

[0021] Stage 3: The temperature was maintained at 190°C, the reactor volume was maintained at 85 mL, and the duration was 110 minutes;

[0022] The fourth stage: the temperature is naturally cooled from 190°C to 90-100°C, the reactor volume is increased from 85mL to 100mL, and the time is 75-125 minutes;

[0023] The fifth stage: the temperature was naturally cooled from 90°C to room temperature, and the volume of the reactor was maintained at 100 mL.

[0024] Furthermore, the centrifugation and washing process in the first, third and fourth steps is to centrifuge the solution at 6600 rpm for 15 minutes, pour off the supernatant to obtain a precipitate, add deionized water and centrifuge, repeat twice to obtain the final precipitate product; the drying temperature in the first, third and fourth steps is 60°C and the time is 8-12h; the calcination temperature in the second and fifth steps is 360°C.

[0025] Furthermore, in the third step, the mass volume ratio of the chain spherical metal oxide powder, aniline and ammonium persulfate is 0.4g:200μL:0.5g; the amount of concentrated hydrochloric acid and deionized water in the third step is 1ml and 40ml respectively; the stirring speed in the third step is 155 rpm; and the drying condition is drying at 60°C for 12 hours.

[0026] Furthermore, in the fourth step, the mass volume ratio of stannous chloride dihydrate, hydrochloric acid and deionized water is 2g:1.4ml:80ml, and the hydrochloric acid is 37% concentrated hydrochloric acid.

[0027] Furthermore, in the sixth step, the mass ratio of the metal oxide chain ball-shaped ternary composite material to polyvinylidene fluoride PVDF is 8:2, and magnetic stirring is performed at a speed of 75 rpm for 8 hours, and the mixture is evenly mixed to form a slurry.

[0028] Furthermore, in the seventh step, the mold is a scraper, the slurry coating thickness is 60-90 microns, and it is dried in a drying oven at 40° C. for 10 hours to obtain a metal oxide chain ball-shaped ternary composite material diaphragm.

[0029] Furthermore, in the eighth step, the mass volume ratio of SnO2 nanoparticles to anhydrous ethanol solution is 0.5g:50mL; 1.5mL of the suspension is used for each filtration, and the diameter of the filtration bottle is 4cm.

[0030] The present application also discloses a lithium-sulfur battery diaphragm with a spherical chain metal oxide structure obtained by any of the above-mentioned preparation methods, wherein the diaphragm on the sulfur cathode side is coated with a metal oxide chain spherical ternary composite material; the metal oxide chain spherical ternary composite material can catalyze the conversion of polysulfides, inhibit the shuttle effect, and improve the diffusion and migration of lithium ions; the lithium anode side of the diaphragm is metal oxide nanoparticles, which can make the lithium anode electric field uniformly distributed and inhibit the irregular growth of lithium dendrites.

[0031] Beneficial effects:

[0032] The present application provides a lithium-sulfur battery separator having a ball-chain metal oxide structure and a preparation method thereof, which has the following beneficial effects compared with the prior art:

[0033] 1. The lithium-sulfur battery separator having a spherical chain metal oxide structure prepared in the present application, the chain conductive material on the sulfur cathode side is used as a conductive framework to provide a fast electron / ion transmission channel, the spherical metal oxide is a polar material, and has a small particle size and good dispersibility. The modified chain conductive material can provide more active sites, can effectively chemically adsorb polysulfides, and can significantly inhibit the shuttling effect of polysulfides between the positive and negative electrodes;

[0034] 2. The lithium-sulfur battery separator with a spherical chain metal oxide structure prepared in the present application, the metal oxide chain spherical ternary composite material on the sulfur cathode side has better hydrophilicity to the electrolyte, enables the electrolyte to diffuse and migrate more quickly, enhances the compatibility with the electrolyte, ensures more efficient migration of lithium ions, accelerates the kinetics of the electrochemical reaction, reduces polarization, and improves the lithium ion conductivity of the battery;

[0035] 3. The lithium-sulfur battery separator having a ball-chain metal oxide structure prepared in the present application, the metal oxide nanoparticles uniformly deposited on the anode side ensure a more uniform distribution of the interface electric field, make the lithium ion concentration uniformly distributed, promote uniform lithium deposition, and reduce dendrite growth;

[0036] 4. The fast ion transport channel on the cathode side and the uniform electric field distribution on the anode side jointly optimize the transport and distribution of lithium ions inside the battery; at the same time, the catalytic effect of the entire structure on the conversion of polysulfides and the acceleration of the electrochemical reaction kinetics enable the battery to perform energy conversion more efficiently during the charge and discharge process, further improving the battery performance;

[0037] 5. Dynamic filling degree regulation of dispersibility Hydrothermal technology effectively improves the dispersibility of materials. By rationally regulating the pressure, volume and other parameters of the reaction system, metal oxide nanoparticles can be more evenly distributed on carbon nanotubes; for example, in the hydrothermal process, the fine control of temperature and volume at different stages avoids the agglomeration of particles caused by excessive local concentration, so that the material presents a better dispersion state; the dynamic hydrothermal method provides a high degree of process controllability, and can flexibly adjust parameters such as filling degree according to the characteristics of the material, thereby achieving precise regulation of the final material properties; for example, by adjusting the pressure and volume changes during the hydrothermal process, the nucleation and growth process of quantum dots can be controlled to make their size distribution more uniform and the dispersion higher, thereby improving the adsorption and catalytic properties of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 is a scanning electron microscope (SEM) image of the metal oxide chain ball-shaped ternary composite material obtained in Example 1 of the present application;

[0039] Figure 2This is a scanning electron microscope (SEM) image of the metal oxide nanoparticles obtained in Example 1 of the present application. DETAILED DESCRIPTION

[0040] In order to facilitate the understanding of the present invention, the principles and features of the present invention are comprehensively and carefully described below in conjunction with the accompanying drawings and preferred embodiments. The embodiments are only used to explain the present invention and are not intended to limit the scope of the present invention.

[0041] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0042] In order to further illustrate the present invention, the lithium-sulfur battery separator with a ball-chain metal oxide structure and the preparation method thereof provided by the present invention are described in detail below in conjunction with examples.

[0043] Example 1

[0044] A method for preparing a lithium-sulfur battery separator having a ball-chain metal oxide structure, comprising the following steps:

[0045] The first step: dissolve 2g of stannous chloride dihydrate in 80mL of deionized water, add 1.4mL of 37% concentrated hydrochloric acid, adjust the pH value to 0.68 to obtain a stannous chloride dihydrate solution, and then immerse 40mg of carbon nanotubes in the stannous chloride dihydrate solution, stir for 1h, centrifuge, wash and disperse in 50mL of deionized water to obtain a dispersion, transfer the dispersion to a RC-HP-CV high-pressure volume variable reactor, and perform hydrothermal treatment according to the method in Table 1. When the reactor temperature drops to room temperature, collect the black product after hydrothermal treatment, wash it three times with deionized water and anhydrous ethanol, transfer it to a vacuum drying oven, and dry it at 60°C for 12h to obtain a SnO2 precursor; the centrifugation and washing process is to centrifuge the solution at 6600 rpm for 15 minutes, pour off the supernatant to obtain a precipitate, add deionized water for centrifugation, repeat twice to obtain the final precipitated product;

[0046] Step 2: Then grind the SnO2 precursor and place it on a quartz boat and place the quartz boat in a tube furnace, then calcine it at 360°C for 2h in an air environment, and after cooling, a chain ball-shaped metal oxide powder can be obtained;

[0047] Step 3: Prepare a mixed solution of concentrated hydrochloric acid and deionized water with 1 mL of concentrated hydrochloric acid and 38 mL of deionized water, take the mixed solution and place it in two beakers, respectively, record it as A and B, add 200 μL of polyaniline drop by drop into beaker A and ultrasonically treat it, and disperse the chain ball-shaped metal oxide powder into the ultrasonically treated solution; add 0.5 g of ammonium persulfate to beaker B and stir to dissolve, then add the solution drop by drop into beaker A, stir at a speed of 155 rpm for 4 hours, centrifuge the solution at 6600 rpm for 15 minutes, pour off the supernatant, and obtain a precipitate. Add deionized water and centrifuge again, repeat twice, and obtain the final precipitated product, a metal oxide chain ball-shaped ternary composite material;

[0048] Figure 1 The scanning electron microscope (SEM) image of the metal oxide chain ball ternary composite material obtained in Example 1 of the present invention shows that PANI wraps the surface of SnO2-CNT, thereby increasing the diameter of the metal oxide chain ball ternary composite material to 25-60nm. A rough surface with many small protruding particles is generated, resulting in a larger specific surface area and increased catalytic sites.

[0049] Step 4: Dissolve 2 g of stannous chloride dihydrate in 80 mL of deionized water, add 1.4 mL of 37% concentrated hydrochloric acid, adjust the pH value to 0.68, stir for 1 h, centrifuge the solution at 6600 rpm for 15 minutes, pour off the supernatant to obtain a precipitate, add deionized water and centrifuge, repeat twice to obtain the final precipitate product, and disperse it in 50 mL of deionized water, then transfer it to a RC-HP-CV high-pressure volume variable reactor, and perform hydrothermal treatment according to Table 1; when the reactor temperature drops to room temperature, collect the white product after hydrothermal treatment, wash it three times with deionized water and anhydrous ethanol, transfer it to a vacuum drying oven, and dry it at 60 ° C for 12 h to obtain a SnO2 precursor;

[0050] Step 5: Grind the SnO2 precursor and place it on a quartz boat, place the quartz boat in a tube furnace, and then calcine it at 360°C for 2h in an air environment. After cooling, SnO2 nanoparticles can be obtained.

[0051] Figure 2 This is a scanning electron microscope (SEM) image of SnO2 obtained in Example 1 of the present invention. The prepared SnO2 nanoparticles show a spherical morphology with a diameter of about 5-10 nm.

[0052] Step 6, preparation of slurry: 0.8 g of the metal oxide chain ball-shaped ternary composite material and 0.2 g of the PVDF binder are magnetically stirred at a speed of 75 rpm for 8 hours, and mixed evenly to form a slurry;

[0053] Step 7: Use a scraper to evenly apply the slurry on the commercial PP separator Celgard 2500, the slurry coating thickness is 60-90 microns, and then transfer Celgard 2500 to a vacuum drying oven and dry it at 40°C for 10 hours to obtain a metal oxide chain ball-shaped ternary composite material separator;

[0054] Step 8: Disperse 0.5 g of SnO2 nanoparticles evenly in 50 mL of anhydrous ethanol solution to form a uniform suspension, and then filter the suspension to the back of the metal oxide chain ball-shaped ternary composite membrane with a suction filtration bottle, and then transfer the membrane to a vacuum drying oven and dry it at 40 ° C for 4 hours;

[0055] The ninth step is the preparation of the diaphragm: the dried diaphragm is cut into small discs with a diameter of 19 mm to obtain a lithium-sulfur battery diaphragm with a ball-chain metal oxide structure.

[0056] Preparation of positive electrode: Sublimed sulfur, conductive carbon black and binder polyvinylidene fluoride were ground and stirred at a speed of 75 rpm for 6 hours to make a slurry. The slurry was evenly coated on the aluminum foil using a mold, and then the aluminum foil was transferred to a vacuum drying oven and dried at 50°C for 10 hours. The dried aluminum foil was cut into small discs with a diameter of 16 mm, which were the positive electrode sheets.

[0057] Preparation of lithium-sulfur battery: The prepared positive electrode sheet and round Celgard 2500 were used as separators, commercial metal lithium sheets were used as negative electrodes, 0.1M LiNO3+1M LiTFSI DOL / DME (volume ratio 1:1) electrolyte was added, and the 2032 button cells were assembled in an argon-filled glove box with a water and oxygen content of less than 0.1ppm. After standing for 12 hours, the assembled batteries were tested for long-cycle electrochemical performance in a battery test cabinet (Neware BTS 7.6.0).

[0058] The present invention discloses a lithium-sulfur battery separator having a ball-chain metal oxide structure and a preparation method thereof. The hydrothermal treatment is performed by placing a chain-shaped conductive material and a metal salt in a reaction device with a controllable volume for hydrothermal treatment. The hydrothermal treatment is divided into five stages, as shown in Table 1.

[0059] Metal oxide nanoparticles need to be distributed as evenly as possible on the chain-like conductive material. In lithium-sulfur battery applications, evenly distributed metal oxide nanoparticles can provide adsorption sites on a larger surface area. Metal oxides can make full use of the larger surface area of ​​the chain-like conductive material to more effectively adsorb LiPSs. Evenly distributed metal oxide nanoparticles can form a relatively stable and uniform catalytic environment on the chain-like conductive material. For the catalytic conversion process of polysulfides, a uniform catalytic environment helps to improve the catalytic efficiency. If the metal oxide nanoparticles are unevenly distributed, it may cause the local catalytic activity to be too high or too low, affecting the overall catalytic conversion effect of polysulfides.

[0060] When metal oxide nanoparticles are evenly distributed on the chain-like conductive material, a more stable interaction can be formed between the particles and the chain-like conductive material. This uniform distribution makes the binding force between the particles and the chain-like conductive material more uniform, which can better withstand external stress and strain and improve the structural stability of the material. It avoids the agglomeration of metal oxide nanoparticles due to excessive local concentration. Particle agglomeration may reduce the specific surface area of ​​the material, affect its adsorption and catalytic properties, and may also destroy the structural stability of the material.

[0061] Generally speaking, when the pressure is low, the molecular distance in the reaction system is relatively large, and the interaction force between molecules is weak. This may lead to a slow diffusion rate of the reactants and a relatively slow nucleation and growth process of quantum dots. There are fewer gas molecules in the reaction system, and the gas phase space is relatively large. This may accelerate the volatilization rate of the solute in the liquid phase, resulting in unstable solute concentration in the quantum dot growth environment, affecting the nucleation and growth process of the quantum dots, making their size distribution uneven and the dispersion decreased. Low pressure may result in fewer nucleation sites for quantum dots and a relatively insufficient nucleation process. This will result in a relatively small number of quantum dots and an uneven distribution. During the growth process, due to the slow diffusion rate of the reactants and the weak interaction between quantum dots, the growth of quantum dots may be incomplete or uneven, thereby affecting their dispersion.

[0062] Under high pressure, the molecular distance in the reaction system decreases and the interaction force between molecules increases. This may accelerate the diffusion rate of the reactants, and the nucleation and growth rate of quantum dots will also accelerate accordingly. High pressure will compress the gas phase space, increase the number of molecules in the gas phase, slow down the volatilization rate of the solute in the liquid phase, and the solute concentration in the quantum dot growth environment will be relatively stable. This will help the uniform nucleation and growth of quantum dots and improve the dispersion of quantum dots. High pressure may increase the nucleation sites of quantum dots and promote the large-scale nucleation of quantum dots. However, if the nucleation rate is too fast, it may cause mutual collision and aggregation between quantum dots, reducing the dispersion.

[0063] Table 1 Temperature and time conditions of each stage of hydrothermal

[0064]

[0065]

[0066] Example 2

[0067] The method is the same as Example 1, except that the metal oxide is iron oxide, iron oxide quantum dots are hydrothermally generated, and the chain-like conductive material is silver nanowires.

[0068] Example 3

[0069] The same as Example 1, except that the metal oxide is aluminum oxide, aluminum oxide quantum dots are hydrothermally generated, and the chain-like conductive material is carbon fiber.

[0070] Example 4

[0071] The same as Example 1, except that the conductive polymer is polypyrrole, the polypyrrole conductive material is used for coating, and the chain-shaped conductive material is carbon nanotube.

[0072] Example 5

[0073] The same as Example 1, except that the metal oxide is niobium pentoxide, the conductive polymer is polyacetylene, and the chain-like conductive material is carbon fiber.

[0074] Comparative Examples 1-4

[0075] The same as Example 1-4, except that the dynamic gas phase atmosphere method is not used for regulation during the hydrothermal treatment. The hydrothermal temperature is 190° C., and the heating rate is 5° C. / min.

[0076] The final prepared metal oxide chain ball-shaped ternary composite material was characterized, and the life and performance of the lithium-sulfur battery assembled with it were tested.

[0077] Table 2 Evaluation of the starting and ending capacity and cycle life of the ternary composite lithium-sulfur battery at 1C using the solution used in the embodiment of the present invention and the prepared metal oxide chain ball

[0078]

[0079] Table 3 Evaluation of the starting and ending capacity and cycle life of the solution used in the embodiments of the present invention and the prepared metal oxide chain ball-shaped ternary composite material lithium-sulfur battery at 1C.

[0080]

[0081] Analysis of the embodiments and comparative examples: By comparing Table 2 and Table 3, it can be found that the materials in the embodiments using the dynamic filling degree regulation and dispersibility hydrothermal technology are generally superior to the control group in terms of dispersibility. Specifically, the materials in Table 2 show a better dispersion state, while the materials in the control group in Table 3 have poor dispersibility. This shows that the dynamic filling degree regulation and dispersibility hydrothermal technology effectively improves the dispersibility of the material, thereby significantly improving the performance of the material. At the same time, the dynamic filling degree regulation and dispersibility hydrothermal technology helps to better regulate the performance of the material. The regulated materials in Table 2 have a significant improvement in dispersibility and performance compared to the unregulated materials in Table 3, indicating that the technology can achieve a better balance between high performance and good dispersibility while improving dispersibility. This means that the dynamic filling degree regulation and dispersibility hydrothermal technology will not sacrifice other properties of the material, but through reasonable filling degree regulation, the stability and performance of the material are better maintained. The dynamic filling degree regulation and dispersibility hydrothermal technology provides a high degree of process controllability, and can flexibly adjust parameters such as filling degree according to the characteristics of the material, thereby achieving precise regulation of the final material performance. This makes the process have a wide range of application potential and can adapt to complex and changeable material preparation needs.

[0082] Test method description:

[0083] (1) The constant current charge and discharge performance test of lithium-sulfur batteries was carried out using the charge and discharge instrument of Shenzhen Xinwei Co., Ltd. In this paper, the test temperature is the ambient temperature of 25°C, the charge and discharge voltage cut-off range is 1.7-2.8V, and the charge and discharge current is set to 1C. The starting capacity is the discharge capacity of the battery at the first discharge, and the end capacity is the previous discharge capacity when the battery cannot be charged and discharged normally.

[0084] (2) Life cycle: Each charge and discharge is a cycle. When the lithium-sulfur battery cannot complete a charge and discharge process normally, or the capacity drops rapidly by more than 50% within 5 cycles, the lithium-sulfur battery can be judged to have ended its life. This rapid capacity drop usually means that serious side reactions have occurred inside the battery or the structure has rapidly deteriorated, resulting in a sharp drop in battery performance that can no longer meet the needs of practical applications. Through such strict judgment criteria, the service life of lithium-sulfur batteries can be accurately determined.

Claims

1. A method for preparing a lithium-sulfur battery separator having a ball-chain metal oxide structure, characterized in that: Here are the steps: The first step: dissolving 2-4 g of metal salt in 80-100 mL of deionized water according to the mass-to-volume ratio, adding acid to adjust the pH value to 0.68 to obtain a metal salt solution, and then immersing 40-60 mg of chain-shaped conductive material in the metal salt solution, stirring for 1 hour, centrifuging, washing and dispersing in 50 mL of deionized water to obtain a dispersion, and transferring the dispersion to a RC-HP-CV high-pressure variable volume reactor for hydrothermal treatment. When the reactor temperature drops to room temperature, the black product after the hydrothermal treatment is collected, washed three times with deionized water and anhydrous ethanol, and transferred to a vacuum drying oven for drying to obtain a precursor of a chain-shaped metal oxide; Step 2: Grind the precursor of the chain ball-shaped metal oxide and place it on a quartz boat, and then place the quartz boat in a tube furnace, and then calcine it in an air environment for 2 hours, and after cooling, obtain the chain ball-shaped metal oxide powder; Step 3: prepare a mixed solution of concentrated hydrochloric acid and deionized water at a volume ratio of 1:38-40, take 39-41 mL of the mixed solution and divide it into two equal parts and place them in two beakers, respectively denoted as A and B, drip 200-300 μL of conductive polymer monomer into beaker A drop by drop and ultrasonically treat it, and disperse the chain ball-shaped metal oxide powder into the ultrasonically treated solution; add 0.5-0.7 g of ammonium persulfate into beaker B and stir to dissolve, then drip the solution into beaker A drop by drop, finally stir for 4 hours, and then obtain the metal oxide chain ball-shaped ternary composite material after centrifugation, washing and drying; Step 4: Dissolve 2-4 g of metal salt in 80-100 mL of deionized water according to the mass-to-volume ratio, add acid to adjust the pH value to 0.68 to obtain a metal salt solution, stir for 1 hour, centrifuge, wash and disperse in 50 mL of deionized water to obtain a dispersion, transfer the dispersion to a RC-HP-CV high-pressure variable volume reactor, perform hydrothermal treatment, collect the product after hydrothermal treatment after the reactor temperature drops to room temperature, wash three times with deionized water and anhydrous ethanol, transfer to a vacuum drying oven, and dry to obtain a precursor of metal oxide nanoparticles; Step 5: Grind the precursor of the metal oxide nanoparticles and place it on a quartz boat, place the quartz boat in a tube furnace, and then calcine it in an air environment for 2 hours, and then cool it to obtain the metal oxide nanoparticles; Step 6, preparation of slurry: magnetically stirring the metal oxide chain ball-shaped ternary composite material and the polyvinylidene fluoride PVDF binder to prepare a slurry after mixing evenly; Step 7: Use a mold to evenly coat the slurry on the commercial PP diaphragm Celgard 2500, and then transfer the Celgard 2500 diaphragm to a drying oven to obtain a metal oxide chain ball-shaped ternary composite diaphragm; Step 8: Disperse 0.5 g of metal oxide nanoparticles in 50 mL of anhydrous ethanol solution according to the mass volume ratio to form a uniform suspension, and then filter the suspension to the back of the metal oxide chain ball-shaped ternary composite membrane with a suction filtration bottle, and then transfer the membrane to a vacuum drying oven and dry it at 40 ° C for 4 hours; Step 9, preparation of the diaphragm: Cut the diaphragm dried in step 8 into small discs with a diameter of 19 mm to obtain a lithium-sulfur battery diaphragm with a ball-chain metal oxide structure.

2. The method for preparing a lithium-sulfur battery separator having a ball-chain metal oxide structure according to claim 1, characterized in that: The metal oxide is one or more of tin oxide, iron oxide, aluminum oxide, vanadium pentoxide, niobium pentoxide, and titanium dioxide; the chain-shaped conductive material is one or more of carbon nanotubes, carbon fibers, silver nanowires, silicon carbide nanowires, and titanium nanowires; the conductive polymer is one or more of polyaniline, polypyrrole, and polyacetylene; the metal salt is one or more of stannous chloride dihydrate, ferric chloride, aluminum chloride hexahydrate, and niobium pentachloride; the acid is concentrated hydrochloric acid, and the concentrated hydrochloric acid is 37% concentrated hydrochloric acid.

3. The method for preparing a lithium-sulfur battery separator having a ball-chain metal oxide structure according to claim 1, characterized in that: The hydrothermal process is specifically as follows: Stage 1: The temperature was raised from room temperature to 120°C at a rate of 5°C / min, the reactor volume was maintained at 65mL, and the time was 20 minutes; The second stage: the temperature was increased from 120°C to 190°C at a heating rate of 2°C / min, the reactor volume was increased from 65mL to 85mL, and the time was 70 minutes; Stage 3: The temperature was maintained at 190°C, the reactor volume was maintained at 85 mL, and the duration was 110 minutes; The fourth stage: the temperature is naturally cooled from 190°C to 90-100°C, the reactor volume is increased from 85mL to 100mL, and the time is 75-125 minutes; The fifth stage: the temperature was naturally cooled from 90°C to room temperature, and the volume of the reactor was maintained at 100 mL.

4. The method for preparing a lithium-sulfur battery separator having a ball-chain metal oxide structure according to claim 1, characterized in that: The centrifugation and washing process in the first step, the third step and the fourth step is to centrifuge the solution at 6600 rpm for 15 minutes, pour off the supernatant to obtain a precipitate, add deionized water and centrifuge again, repeat twice to obtain the final precipitate product; The drying temperature in the first step, the third step and the fourth step is 60°C and the drying time is 8-12 hours; the calcination temperature in the second step and the fifth step is 360°C.

5. The method for preparing a lithium-sulfur battery separator having a ball-chain metal oxide structure according to claim 1, characterized in that: In the third step, the mass volume ratio of the chain spherical metal oxide powder, aniline and ammonium persulfate is 0.4g:200μL:0.5g; the amount of concentrated hydrochloric acid and deionized water in the third step is 1ml and 40ml respectively; the stirring speed in the third step is 155 rpm; and the drying condition is 60°C drying for 12 hours.

6. The method for preparing a lithium-sulfur battery separator having a ball-chain metal oxide structure according to claim 1, characterized in that: In the fourth step, the mass volume ratio of stannous chloride dihydrate, hydrochloric acid and deionized water is 2g:1.4ml:80ml, and the hydrochloric acid is 37% concentrated hydrochloric acid.

7. The method for preparing a lithium-sulfur battery separator having a ball-chain metal oxide structure according to claim 1, characterized in that: In the sixth step, the mass ratio of the metal oxide chain ball-shaped ternary composite material to polyvinylidene fluoride PVDF is 8:2, and magnetic stirring is performed at a speed of 75 rpm for 8 hours to prepare a slurry after uniform mixing.

8. The method for preparing a lithium-sulfur battery separator having a ball-chain metal oxide structure according to claim 1, characterized in that: In the seventh step, the mold is a scraper, the slurry coating thickness is 60-90 microns, and the slurry is dried in a drying oven at 40° C. for 10 hours to obtain a metal oxide chain ball-shaped ternary composite material diaphragm.

9. The method for preparing a lithium-sulfur battery separator having a ball-chain metal oxide structure according to claim 1, characterized in that: In the eighth step, the mass volume ratio of SnO2 nanoparticles to anhydrous ethanol solution is 0.5g:50mL; 1.5mL of the suspension is used for each filtration, and the diameter of the filtration bottle is 4cm.

10. A lithium-sulfur battery separator having a ball-chain metal oxide structure obtained by any preparation method according to any one of claims 1 to 9, characterized in that: The sulfur cathode side diaphragm is coated with a metal oxide chain ball-shaped ternary composite material; the metal oxide chain ball-shaped ternary composite material can catalyze the conversion of polysulfides, inhibit the shuttle effect, and improve the diffusion and migration of lithium ions; the lithium anode side of the diaphragm is metal oxide nanoparticles, which can make the lithium anode electric field evenly distributed and inhibit the irregular growth of lithium dendrites.

Citation Information

Patent Citations

  • Preparation method for modified diaphragm for lithium-sulfur battery, modified diaphragm and lithium-sulfur battery adopting modified diaphragm

    CN105489818A

  • Regenerative polysulfide-scavenging layers enabling lithium-sulfur batteries with high energy density and prolonged cycling life and methods of making same

    US20180241039A1